In vitro embryonic development and conception rate of vitrified bovine oocytes (Bos indicus) in mature stage - Briceño, Yander M. (2020)
In vitro embryonic development and conception rate of bovine oocytes (Bos indicus) vitrified in mature stage were evaluated. The ovaries were collected from Brahman cows from the Bagua Grande municipal slaughterhouse (Amazonas, Peru). The collected ovaries were transferred to the laboratory in 0.9% NaCl solution with 0.025 mg/ml streptomycin. The oocytes were aspirated, matured in vitro and vitrified. The nuclear stage of the oocytes was determined with aceto-orcein staining. Among them, 12.5% exhibited germinal vesicle, 5% reached metaphase I (MI) and 82.5% reached metaphase II (MII) of nuclear stage. The potential for embryonic development was evaluated on day 7 of the in vitro culture. It was obtained 5.8% of morulae and 10.4% blastocysts in the experimental group (n=154 vitrified oocytes) and 11.6% of morulae morulae and 24.9% of blastocysts in the control group (n=181 oocytes without vitrification process). Finally, 14 embryos produced from vitrified oocytes were transferred in recipient cows, reaching the embryonic vesicle 35 days after transfer in three cows (21.4%).